The Role of Social Media in Building Corporate Image: A Qualitative Study of @rahmahtravel.id's Communication Strategy on Instagram - Rofian Dedi Susanto; Ido Afriadi (Universitas Muhammadiyah Metro, 2026)
This research is motivated by the paradigm shift of corporate communication to digital platforms, specifically the strategic role of Instagram in the religious travel industry to build public trust and corporate image. The purpose of this study is to analyze the communication strategy of the @rahmahtravel.id account, identify the visual and narrative elements shaping its corporate image, and explain Instagram's contribution to this image formation. The research method used is qualitative with a constructivism paradigm. Data was collected through upload observation, documentation, and literature study, and subsequently analyzed using qualitative content analysis focusing on integrated visual-verbal discourse. The results show that @rahmahtravel.id's communication strategy is built upon a harmonious synergy between visual aesthetics (representation of collective piety and professional facilities) and the power of linguistic narratives (the use of spiritual metaphors, lexicons of trust, and warm imperative structures). Instagram contributes by transforming monological communication patterns into participatory interactions (co-creation of meaning). The impact of this research provides empirical evidence that intersemiotic integration on social media effectively projects a religious and professional corporate image, which serves as a crucial foundation for safeguarding the company's reputation from trust crises while building long-term customer loyalty.